Can neutral clusters: a two-step G0W0 and DFT benchmark - Bakhsh, Sunila; Aslam, Sameen; Khalid, Muhammad; Sohail, Muhammad; Zafar, Sundas; Wadood, Sumayya Abdul; Morsy, Kareem; Iqbal, Muhammad Aamir (Beilstein Journal of Nanotechnology, 2024)
Electronic and structural properties of calcium clusters with a varying size range of 2–20 atoms are studied using a two-step scheme within the GW and density functional theory (DFT) with generalized gradient approximation (GGA). The GGA overestimates the binding energies, optimized geometries, electron affinities, and ionization potentials reported in the benchmark. The ground-state structure geometry and binding energy were obtained from the DFT for the ground-state structure of each cluster. The binding energy of the neutral clusters of the calcium series follows an increasing trend, except for a few stable even and odd clusters. The electronic properties of the calcium cluster were studied with an all-electron FHI-aims code. In the G0W0 calculation, the magic cluster Ca10 has relatively high ionization potential and low electron affinity. The obtained ionization potentials from the G0W0@PBE calculation showed that the larger cluster has less variation, whereas the electron affinities of the series have an increasing trend. The ionization potentials from the G0W0 benchmark for the calcium cluster series have not yet been described in the literature.
Keywords: calcium clusters; density functional theory; G0W0 approximation; ionization potentials; magic clusters